2019
DOI: 10.1002/ccr3.2542
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Schwannoma: In light of a case report

Abstract: A 41‐year‐old man with abdominal enlargement, as a result of large retroperitoneal Schwannoma, was reported to our center. It was seen to have caused the displacement of the colon and was attached to the presacral region of the spine. Following the diagnosis, successful resection of Schwannoma was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Tumors involving the peripheral nerves are usually asymptomatic, while tumors involving spinal nerve roots commonly present with radicular pain and nerve compression syndromes. 1 , 3 Histologically, they appear as encapsulated masses with a soft tan-white appearance with or without focal areas of cystic degenerative changes of Antoni A (hypercellular) areas and Antoni B (hypocellular) areas, respectively. In immunohistochemistry, the presence of S100 protein is a classic marker for diagnostic confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors involving the peripheral nerves are usually asymptomatic, while tumors involving spinal nerve roots commonly present with radicular pain and nerve compression syndromes. 1 , 3 Histologically, they appear as encapsulated masses with a soft tan-white appearance with or without focal areas of cystic degenerative changes of Antoni A (hypercellular) areas and Antoni B (hypocellular) areas, respectively. In immunohistochemistry, the presence of S100 protein is a classic marker for diagnostic confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors originate in cranial, peripheral, or visceral nerves at all anatomical locations. 1 Head, neck, mediastinum, retroperitoneal, and extremities are the most common places for schwannomas to grow. In contrast, they rarely occur in the pelvis with a reported incidence of 1–3% and typically associated with neurofibromatosis type 1 (von Recklinghousen disease), less than 0.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Schwannomas or the so-called neuromas are known as benign tumors that arise from the Schwann cells of nerve fibers [8,9]. These tumors are rarely malignant (<1% of cases) [10] and are frequently found in the head, neck and mediastinum, but sometimes also at the level of the extremities [11,12]. Studies have shown that the pelvic location of schwannomas is very rare (3%) and in this case, they emerge from the sacral nerve or hypogastric plexus [12].…”
Section:  Schwannomasmentioning
confidence: 99%
“…These tumors are rarely malignant (<1% of cases) [10] and are frequently found in the head, neck and mediastinum, but sometimes also at the level of the extremities [11,12]. Studies have shown that the pelvic location of schwannomas is very rare (3%) and in this case, they emerge from the sacral nerve or hypogastric plexus [12]. Sacral schwannomas can be classified in three categories: type I -when the tumor is confined to the sacrum; type II -when the tumor arise from the sacrum but involve also pre-sacral or subcutaneous space; type III -the tumor is located in the pelvis or retroperitoneum [13].…”
Section:  Schwannomasmentioning
confidence: 99%
See 1 more Smart Citation